Gerakan Satu Juta Tumbler: Persepsi Aparatur Sipil Negara Terhadap Penggunaan 1 Tumbler dan Pengurangan Sampah Plastik - Ane Dwi Septina, S.Sos, MA; Surendro Pradipto; Mirna Aulia Pribadi (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2023)
One of the Indonesian government's steps to overcome plastic waste problem is by initiating The One Million Tumbler Movement campaign. The Civil Servant as a government agent have to had good knowledge and applying this policy in their lives and their environment. This is a case study approach to gather primary data and secondary data through in-depth interviews, field observation in the Centre for Research and Development on Social, Economy, Policy and Climate Change (P3SEKPI), Bogor and literature study. The informant of this study was P3SEKPI civil servants with structural and functional career background with a total informant of 4 people. The result showed that the civil servant have knowledge about plastic waste reduction and have supportive perception in tumblers use. The P3SEKPI's management supports the tumbler's use as new habits related to The One Million Tumbler Movement campaign. The family values on environment characterize the tumbler and plastic bag uses in general. However, although the civil servant's environmental awareness has formed, the Covid-19 pandemic has made plastic consumption unavoidable.The support from environment (The management and the family environment) is essential to helps civil servants continue on habit implementation of tumbler use in particular and the plastic awareness movement in general. If all this support is strengthened, it is possible to help increase the individual's environmental awareness in daily activities.